Duodenal neuroendocrine tumors: Short-term outcomes of endoscopic submucosal dissection performed in the Western setting - Gupta, Sunil; Kumar, Puja; Chacchi, Rocio; Murino, Alberto; Despott, Edward J; Lemmers, Arnaud; Pioche, Mathieu; Bourke, Michael J. (Endoscopy International Open, 2023)
Background and study aims Endoscopic resection (ER) is recommended for the management of duodenal neuroendocrine tumors (D-NETs) confined to the submucosal layer, without lymph node or distant metastasis. While this is accepted practice for lesions < 10 mm, consensus for larger lesions remains unclear. Although endoscopic submucosal dissection (ESD) has been proposed as the preferred ER technique for DNETs ≥10 mm, there are limited data on efficacy and safety, particularly in the Western setting.Patients and methods We performed a retrospective analysis of patients with D-NETs who underwent ESD between 2012 and 2022 in three tertiary referral centers in Australia, France, and Belgium.Results Fourteen patients with 15 D-NETs were evaluated. Median patient age was 64 years (interquartile range [IQR] 58–70 years). All D-NETs were confined to the duodenal bulb. Median D-NET size was 10 mm (IQR 7–12 mm) and specimen size was 15 mm (IQR 15–20 mm). Median procedure time was 60 minutes (IQR 25–90 minutes). The rate of en bloc resection was 100%. Intra-procedural perforation occurred in four patients (26.7%), with all closed endoscopically without long-term sequelae. There were no episodes of clinically significant bleeding. No local recurrence, lymph node or distant metastasis was observed at a median follow-up of 19.9 months (IQR 10.3–49.3 months).Conclusions In experienced hands, ESD for D-NETs can achieve a 100% en bloc resection rate. There were no cases of local recurrence or distant metastatic spread, indicating that ESD may be a viable option for patients with D-NETs 10 to 15 mm that are not surgical candidates.
Keywords: Neoplasia; Quality and logistical aspects; Performance and complications; GI Pathology